Comparative study of health (metabolic biomarkers) between owner farmers and farm workers during the COVID-19 pandemic - Dwi Sarwani Sri Rejeki; Dwita Darmawati; Dyah Susanti; Muhammad Zaenuri Syamsu Hidayat; Solikhah Solikhah (International Journal of Public Health Science (IJPHS), 2023)
Differences of land ownership statuses between farmers who grow their land and workers with a profit-sharing system will result in income disparities. The low income received due to reduced levels of rice productivity affects the health status of farmers. Therefore, this study compares the health status between farmers who are owners and workers during the COVID-19 pandemic. In April 2022, this cross-sectional study was carried out in Banyumas Regency, Central Java, Indonesia. Hb, fasting glucose, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, triglycerides, uric acid, blood pressure, and body mass index (BMI) were all assessed in a total of 100 farmers. Blood samples were taken at 3 cc using an ethylenediaminetetraacetic acid (EDTA) anticoagulant vacutainer tube and 5 cc using a plain vacutainer tube, then analyzed in PRODIA Laboratory. A validated tool was used to check blood pressure and BMI. Furthermore, 74% of the 100 farmers surveyed are farm owners, while 26% are workers. The results show that there is no difference in the health status of owners and workers on metabolic biomarkers including Hb, fasting glucose, LDL cholesterol, HDL cholesterol, triglycerides, uric acid, systolic/systole blood pressure, and BMI. In addition, a number of biomarker indicators, including Hb, fasting glucose, LDL cholesterol, triglycerides, and blood pressure, were found to surpass the threshold. Therefore, farmers need to maintain their health status by performing physical activity, consuming healthy food, and reducing their exposure to insecticides with personal protective equipment (PPE) to prevent metabolic diseases in the future.